The role of physical culture and sport activities in migrant integration - Vladimir Alexandrovich Tarasov (Вестник Майкопского государственного технологического университета)
The relevance of the research topic consists in solving the scientific and practical problem of integrating migrants into the host community. The purpose of the research is to identify the role of physical culture and sports in the social integration of migrants. The methodology of the research is presented by the theories of assimilation of migrants with the local population; multiculturalism as the idea of the existence of a multinational state; transnationalism implemented in the conditions of globalization, informatization and digitalization of the society. The research methods used are content analysis of documents; analysis of statistical data, secondary analysis of sociological data, comparative analysis. The novelty of the research issue lies in the critical understanding of the advantages and limitations of physical training and sports as tools for integrating migrants into host communities in foreign countries. The results of the research have been defined: the role of physical training and sports activities in the process of migrants’ integration based on the domestic and foreign research; the main approaches to the implementation of migration policy measures in world practice (assimilation, multiculturalism and transnationalism) as well as the assessment of its success, by using the Migrant Integration Index. The study allows us to draw a conclusion about the dual nature of the integration potential of physical culture and sports in the implementation of migration policy: on the one hand, it is a way of revealing socio-cultural capital, searching for additional opportunities for self-realization in a new socio-cultural environment, overcoming social isolation, eliminating barriers of social exclusion; on the other hand, it is a deterrent effect of migrants’ age, gender, ethnicity, religion, level of education, attitude to various sports and physical activity in the countries of entry and exit on the integration process.